2016
DOI: 10.4236/ijg.2016.78074
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Prospect Definition Using Well and 4D Seismic Data in a Niger Delta Field

Abstract: We carried out time-lapse analysis in a producing Niger Delta X-field, by first investigating the response and sensitivity of rock properties/attributes to lithology and pore fill in 3-D cross plot domain and by Gassmann's fluid substitution modeling. Furthermore, 4-D seismic data were inverted into acoustic impedance volumes through model based inversion scheme. This served as input into a multi-attribute neural network algorithm for the extraction of rock attribute volumes based on the results of the petroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 8 publications
(7 reference statements)
0
6
0
Order By: Relevance
“…This makes Lambda-Rho a better fluid indicator than Mu-Rho which is a matrix indicator that helps to provide direct geological meaningful information about reservoirs [10]. The hydrocarbon zone showed the gas zone lower in Lambda-Rho and density responses than the oil zone [2,10,[39][40][41]. The plot indicates that λρ is more robust than μρ in the analysis of fluids in the field of study and that μρ values are relatively low for the reservoir sand according to [2,3,10].…”
Section: Lambda-rho Against Mu-rhomentioning
confidence: 99%
“…This makes Lambda-Rho a better fluid indicator than Mu-Rho which is a matrix indicator that helps to provide direct geological meaningful information about reservoirs [10]. The hydrocarbon zone showed the gas zone lower in Lambda-Rho and density responses than the oil zone [2,10,[39][40][41]. The plot indicates that λρ is more robust than μρ in the analysis of fluids in the field of study and that μρ values are relatively low for the reservoir sand according to [2,3,10].…”
Section: Lambda-rho Against Mu-rhomentioning
confidence: 99%
“…Withdraw of mass (hydrocarbon) is expected to result in compaction and pressure changes in the reservoir. [2] demonstrated that changes in the rock derived attributes (density, lambda-rho, impedance) indicated change in reservoir properties of a Niger Delta Field (pore saturation and pressure). Similarly, ground subsidence due to hydrocarbon extraction was inferred from evaluating density, lambda-rho and acoustic impedance changes [3].…”
Section: Introductionmentioning
confidence: 98%
“…Estimation of geomechanical properties in the Niger Delta Basin using prestack timemigrated seismic data and well log requires great skill and immense understanding of seismic inversion technique as this is the key to unraveling geomechanical properties from seismic data. Seismic inversion method provides the most detailed view of the earth's subsurface and its applications in the Niger Delta over the years have yielded increase in oil production (Dagogo et al 2016;Akpan et al 2020a, b).…”
Section: Introductionmentioning
confidence: 99%